BRS 372 and BRS 416: high-yielding cotton cultivars with multiple disease resistance - Suassuna,Nelson Dias (2020)
Abstract BRS 372 and BRS 416 are cotton cultivars with high lint yield and genetic resistance to the main cotton diseases in Brazil, particularly to Ramularia Leaf Spot. They have stable yields, good fiber quality and can contribute to a sustainable cotton disease management in tropical environments.